Pendampingan peningkatan daya saing usaha kupi Aceh di Medan melalui manajemen praktis - Dedy Lazuardi; Ihdina Gustina; Putri Wahyuni (Lebah, 2026)
This community service project aims to bridge the managerial gap in traditional Kupi Aceh businesses in Medan City through intensive assistance in implementing practical management, thereby enhancing competitiveness without diminishing its cultural identity. The project adopted a modified Participatory Action Research (PAR) framework, involving 5 partner Kupi Aceh coffee shops with 15 participants. The intervention phases encompassed problem diagnostics, offline training, and on-site mentoring for four weeks. The effectiveness of cognitive understanding was measured using Normalized Gain (N-Gain), while the operational impact was assessed through observations of raw material inefficiency trends. The results indicated a significant increase in managerial literacy, demonstrated by the participants' average N-Gain scores falling into the medium-to-high category (0.64–0.80). Operationally, compliance with cloud-based digital bookkeeping applications and the implementation of standard operating procedures (SOP) successfully enhanced the partners' competitiveness indicators. This was reflected in daily cash flow transparency, the mitigation of fraud risks, and a drastic reduction in raw material inventory inefficiencies by preventing overstock and stock-out risks. In conclusion, the implementation of adaptive practical management is proven effective in transforming family-run governance into a more systematic and efficient structure. Operational standardization and digitalization serve as robust catalysts for the competitiveness of traditional culinary MSMEs amidst modern market disruptions.